2018
DOI: 10.1159/000490760
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Hyperosmolarity in the Intervertebral Disc on the Proliferation and Chondrogenic Differentiation of Nucleus Pulposus-Derived Mesenchymal Stem Cells

Abstract: Nucleus pulposus-derived mesenchymal stem cells (NP-MSCs) are suitable cell candidates for intervertebral disc (IVD) regeneration. However, little work has been done to determine the proliferation and chondrogenic differentiation of NP-MSCs in the hyperosmotic microenvironment of IVD. This study aimed to investigate the influence of the hyperosmolarity of IVD on the proliferation and chondrogenic differ­entiation of NP-MSCs. NP-MSCs were cultured in media of 300, 400, 430, and 500 mOsm/L, mimicking the osmotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 34 publications
2
21
0
Order By: Relevance
“…In a recent 5 Stem Cells International study, Li et al showed that exposing NP-MSCs to osmotic pressures mimicking the healthy IVD environment (430-500 mOsm/L) resulted in a decrease of cell proliferation and chondrogenic differentiation via activation of the ERK pathway, while the relative hypoosmotic condition of mild IDD proved to increase NP-MSC proliferation and chondrogenic potential. Based on this study, a degenerative microenvironment, due to lower osmotic pressures, may be less hostile to NP-MSCs, providing an interesting insight for future regenerative strategies [104].…”
Section: Low Glucose Concentrationmentioning
confidence: 89%
See 1 more Smart Citation
“…In a recent 5 Stem Cells International study, Li et al showed that exposing NP-MSCs to osmotic pressures mimicking the healthy IVD environment (430-500 mOsm/L) resulted in a decrease of cell proliferation and chondrogenic differentiation via activation of the ERK pathway, while the relative hypoosmotic condition of mild IDD proved to increase NP-MSC proliferation and chondrogenic potential. Based on this study, a degenerative microenvironment, due to lower osmotic pressures, may be less hostile to NP-MSCs, providing an interesting insight for future regenerative strategies [104].…”
Section: Low Glucose Concentrationmentioning
confidence: 89%
“…Hyperosmolarity has been demonstrated to induce progenitor cell differentiation towards a mature NP phenotype [104].…”
Section: Hyperosmolaritymentioning
confidence: 99%
“…Thereafter, several researchers have reported the presence of cells compatible with MSCs from NP, AF, and CEP of normal or degenerated IVDs . Further, several microenvironments of IVDs, such as extracellular matrix stiffness, pH, and osmotic pressure, have been shown to affect the properties of these progenitors …”
Section: Intervertebral Disc Progenitorsmentioning
confidence: 99%
“…[107][108][109][110][111][112][113] Further, several microenvironments of IVDs, such as extracellular matrix stiffness, pH, and osmotic pressure, have been shown to affect the properties of these progenitors. [114][115][116] Sakai et al identified NP progenitors with novel NP-specific cell markers, and demonstrated that these progenitors are exhausted with aging and degeneration. 117 Using colony-forming assay with methylcellulose semi-solid medium, they identified progenitors from human and mouse NPs that express tyrosine-protein kinase receptor (Tie2) and disialoganglioside 2 (GD2).…”
Section: Ivd Specific Progenitors In Vitromentioning
confidence: 99%
“…Then, they migrate to degenerative IVD tissues to differentiate into IVD cells to replace the damaged resident cells and (or) protect the damaged cells by some mediators [13]. However, during the process of endogenous repair, IVD-derived MSCs are inevitably exposed to the hostile microenvironments in IVD, including oxidative stress [14], excessive compression [15], acidic pH [16], hypoxia [17], limited nutrition [18], and high osmolarity [19]. These adverse microenvironments can significantly hinder the endogenous repair process by inhibiting the biological behaviors of IVD-derived MSCs and decreasing the number of the cells, and then finally lead to the failure of endogenous repair [13,20].…”
Section: Introductionmentioning
confidence: 99%